ANALISIS PENGARUH NILAI PATRIARKI TERHADAP PRAKTIK PERKAWINAN DINI DAN RENDAHNYA PENDIDIKAN PEREMPUAN DI DAERAH KAPTEN JAMIN LUBIS MEDAN - Desy Greace Sidebang; Ester Mega Rani Br Sinuhaji; Jeta Amina Siahaan; Sonya Febiola; Wahyu Nur Ihsan; Maria Benedic (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This qualitative research using a case study method aims to analyze the influence of strong patriarchal values on the practice of early marriage and limited access to education for women in Kapten Jamin Lubis, Medan. Data was collected through in-depth interviews with key informants, including affected women, parents, and community leaders.The main findings indicate that patriarchal culture places women in a subordinate position, thus their primary role is considered limited to domestic affairs. The practice of early marriage is reinforced by family pressure, economic factors (to reduce the burden of responsibilities), and social pressure/community norms. The impacts of this practice are very real, including the interruption of women’s education, limited employment opportunities, and the reproduction of the cycle of poverty. This study concludes that early marriage in this area is a structural problem rooted in the interaction of culture, economics, and patriarchal social norms.